Perencanaan Strategis Sistem Informasi Pada CV Warisan Pusaka Menggunakan Metode Ward And Peppard - Ricoida, Desy Iba; Savitri, Nabila; Sastika, Dwi Apriyanti; Nadhira, Debby Dhia (MDP Student Conference, 2024)
CV Warisan Pusaka is a business providing services for relocation and delivery of goods to short and long distance locations. CV Warisan Pusaka was founded in 1981 and only provides goods relocation services for companies and runs the company using large trucks. The process of inputting CV Warisan Pusaka data is still done manually. The process of manually inputting data carried out in books has many advantages, namely that errors frequently occur in inputting data, the time required for inputting data takes a long time, filling in data with the same information repeatedly and human factors that are prone to making errors. This makes the data recap process stop every month. Planning strategies can help companies achieve their existing vision and mission so that the company can develop further with the help of IS/IT business strategy planning at CV Warisan Pusaka.